Curricular Cartographies and Imaginaries of University Teaching: The Case of the Master's Program in Education with an Emphasis on University Teaching from the Department of Educology of CIDE - Mora Ramírez, Andrés (2015)
This essay describes presents and discusses the main findings of a research project on the curriculum of the master's degree in Education with a concentration in higher education of the “Division de Educologia del CIDE;” this research was carried out from a Latin American perspective of socio-cultural critical analysis. Although the postgraduate has made a valuable contribution to the professionalization of university faculty, the study found that the curriculum is suffering from a series of uncertainties at the level of its philosophical, pedagogical, and epistemological options as well as the characterization of its subject matter, all of which are due to the absence of deep curricular reconstructions throughout its more than 15 years of existence. In this sense, it is recommended to consider the formulation of a new curriculum that meets the current expectations of society and incorporates the perspectives of the Latin American pedagogical thinking.